How to add education information to your ORCID record. - Open Researcher and Contributor ID (ORCID) (My University, 2021)
The Education and qualifications section of your ORCID record is for information about organizations where you have studied and/or that have awarded you an educational or professional qualification. You can add information about your education or qualifications you have received to your ORCID record manually, and we also strongly encourage you to grant trusted organizations and trusted individuals permission to add and edit information about your affiliation with them.
Keywords: ORCID